Palaeoenvironmental dynamics at the southern Alpine foothills between the Neolithic and the Bronze Age onset. A multi-proxy study from Bande di Cavriana (Mantua, Italy). (1st October 2019) - Zanon, Marco; Unkel, Ingmar; Andersen, Nils; Kirleis, Wiebke
Abstract: The onset of the Bronze Age (approximately 4150 yrs cal. BP) in the southern Lake Garda region (N-Italy) is marked by an increase in the number of settlements and by the widespread adoption of pile-dwelling building techniques. The prominence of this phenomenon polarized the attention of local palaeoenvironmental investigations. As a result, pre-Bronze age landscape and climate dynamics have been investigated to a lesser degree. In an attempt to address this disparity, our contribution focuses on the period between ∼7100 and ∼3800 yrs cal. BP, i.e. approximately between Early Neolithic and Early Bronze Age. The location of our analysis is the former lake of Bande di Cavriana (Mantua). Multi-proxy investigations highlight few major climatic shifts prior to the Bronze Age onset. A first transition into more warm/dry conditions is recorded between ∼6300 and 6100 yrs cal. BP. Similar conditions occur again after ∼4600 yrs cal. BP, peaking at ∼4300 yrs cal. BP. Speculatively, taking into account dating uncertainties, this second shift might represent the local expression of the '4.2Ka' event. A marked transition into a colder/more humid situation occurs then after ∼4300 yrs cal. BP and persists into the Bronze Age. Major vegetational changes begin during the Neolithic with the steady rise of Carpinus betulus pollen (from ∼5700 yrs cal. BP). A more rapid expansion of this taxon after ∼5100 yrs cal. BP might reflect shifts in forest exploitation strategies during the Copper Age (e.g. coppicing) or changes in the ruminant fauna (e.g. grazing vs. browsing habits), arguably due to human intervention. Nonetheless, pollen grains of anthropogenic indicators appear with consistent frequency only since the Bronze Age. The establishment of the Bande di Cavriana pile dwelling (∼3950 yrs cal. BP) is marked by declining arboreal pollen values and growing anthropogenic taxa. This behavior likely reflects a more intense landscape exploitation (deforestation, expansion of arable fields and meadows), although an influx of herbaceous pollen from near-site activities (e.g. cereal processing, garbage dumping) should not be overlooked. Highlights: Climate and land cover changes are investigated between ∼7100 and 3800 cal. BP. A first transition into warmer/more arid conditions occurs between ∼6300 and 6100 cal. BP. A second warm/arid event begins ∼4600 cal. BP and peaks at ∼4300 cal. BP. The Carpinus betulus rise after ∼5100 cal. BP was arguably favored by human intervention. The Bronze Age onset (∼4150 cal. BP) occurs during a marked colder/wetter shift.